2024
DOI: 10.1186/s12967-024-05104-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential anti-tumor effects of regulatory T cells in the tumor microenvironment: a review

Yu Li,
Cangang Zhang,
Aimin Jiang
et al.

Abstract: Regulatory T cells (Tregs) expressing the transcription factor FoxP3 are essential for maintaining immunological balance and are a significant component of the immunosuppressive tumor microenvironment (TME). Single-cell RNA sequencing (ScRNA-seq) technology has shown that Tregs exhibit significant plasticity and functional diversity in various tumors within the TME. This results in Tregs playing a dual role in the TME, which is not always centered around supporting tumor progression as typically believed. Abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 189 publications
0
3
0
Order By: Relevance
“…It has been shown that CTSW is highly expressed in peripheral derived regulatory T cells (pTreg) cells and plays an important role in inhibiting pTreg cell differentiation and function ( Li et al, 2023 ). And numerous experiments have shown that Treg cells not only inhibit anti-tumor immune responses, but also promote tumor microenvironmental vascular regeneration ( Chaudary and Hill, 2007 ; Kim et al, 2020 ; Li et al, 2024 ). Thus CTSW may inhibit tumor development by suppressing Treg cell proliferation, which requires further experimental demonstration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CTSW is highly expressed in peripheral derived regulatory T cells (pTreg) cells and plays an important role in inhibiting pTreg cell differentiation and function ( Li et al, 2023 ). And numerous experiments have shown that Treg cells not only inhibit anti-tumor immune responses, but also promote tumor microenvironmental vascular regeneration ( Chaudary and Hill, 2007 ; Kim et al, 2020 ; Li et al, 2024 ). Thus CTSW may inhibit tumor development by suppressing Treg cell proliferation, which requires further experimental demonstration.…”
Section: Discussionmentioning
confidence: 99%
“…Through the suppression of other immune cells, Treg maintain immunological homeostasis and self-tolerance in typical conditions ( 2 ). The immunosuppressive activity of Treg serves a dual function in both the initiation and progression of tumors ( 3 , 4 ).…”
mentioning
confidence: 99%
“…Through the suppression of other immune cells, Treg maintain immunological homeostasis and selftolerance in typical conditions (2). The immunosuppressive activity of Treg serves a dual function in both the initiation and progression of tumors (3,4).Recent studies have shown that specific signaling molecules present within the TME can induce reprogramming of inflammatory Treg (5). This reprogramming may lead to a shift of inflammatory Treg from a normal immune regulatory phenotype to one that facilitates tumor progression.…”
mentioning
confidence: 99%